Problematika Penerapan Metode Yanbu’a di Pondok Pesantren Tanwirul Qulub Sungelebak Karanggeneng Lamongan (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
This research is framed in the topic of the application of the Yanbu'a Method in Islamic Boarding Schools. The world of education is currently faced with various changes in aspects of life in society. This is due to the rapid advancement of knowledge and technology, as well as the impact of globalization that is occurring in the world. This has an impact on religious education, especially in the teaching of the Qur'an. Not a few Qur'an teachers teach how to read the Qur'an not in accordance with the tajwid or makhorijul huruf that has been taught by the Prophet Muhammad. In addition, there is one of the most prominent obstacles in the implementation of Qur'an reading education, namely in terms of the use of Qur'an teaching methods. This is very urgent to be studied because the application of inappropriate Qur'an teaching methods can result in fatal errors in the way of reading the Qur'an. research, guided by Max Weber's qualitative approach to Verstehen theory, concluded that the obstacles encountered in implementing the Yanbu'a Method were a lack of coordination between teachers, significant differences in student abilities, low student discipline in muroja'ah (religious study), and students' busy schedules outside of Quranic study hours. Optimization of the Yanbu'a Method at Tanwirul Qulub Islamic Boarding School includes teacher training and education, grouping students based on ability, strengthening evaluation and monitoring, providing learning facilities and media, consistent lesson scheduling, and increasing student motivation.